2018
DOI: 10.1080/09540121.2018.1533229
|View full text |Cite
|
Sign up to set email alerts
|

Pre-exposure prophylaxis sorting among men who have sex with men

Abstract: Persson, A. (2014). "I don't blame that guy that gave it to me": Contested discourses of victimisation and culpability in the narratives of heterosexual women infected with HIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Those measures are beyond the scope of this article. Additional questions about affiliative intent were also asked about the characters in these vignettes, however these measures are reported in another article (Martinez & Jonas, 2019). Thus, we report all pertinent measures, manipulations, and exclusions in this study, and the full sample was collected before data analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those measures are beyond the scope of this article. Additional questions about affiliative intent were also asked about the characters in these vignettes, however these measures are reported in another article (Martinez & Jonas, 2019). Thus, we report all pertinent measures, manipulations, and exclusions in this study, and the full sample was collected before data analysis.…”
Section: Methodsmentioning
confidence: 99%
“…As such, one consideration for an individual thinking about starting PrEP may be how others will perceive them and the consequences of those perceptions. For example, knowledge of someone's PrEP use influences decisions about potentially having sex with that person (i.e., PrEP sorting) among MSM (Martinez & Jonas, 2019). This social component invites the possibility that specific evaluative dimensions underlie PrEP judgments, that PrEP judgments may operate at a relational level, and that this relational aspect may activate associative cognitive mechanisms that exacerbate consequences of PrEP judgments.…”
Section: Practical and Social Barriers To Prep Usementioning
confidence: 99%
“…Those measures are beyond the scope of this paper. Additional questions about affiliative intent were also asked about the characters in these vignettes, however these measures are reported in another paper (Martinez & Jonas, 2019). Thus, we report all pertinent measures, manipulations, and exclusions in this study and the full sample was collected before data analysis.…”
Section: Methodsmentioning
confidence: 99%
“…PrEP users also report feeling stigmatized as a result of being rejected for sex dates or by being seen as HIV positive [44]. On the other hand, PrEP users can also be preferred as sex partners by MSM who are not using PrEP, as they are potentially at lower risk of transmitting HIV [45]. PrEP users have also been seen as more responsible and trustworthy, and their use of PrEP was not itself perceived as a reflection of sexual promiscuity [46].…”
Section: Community Responsesmentioning
confidence: 99%
“…For example, they were seen as more desirable sex partners. It has been suggested that PrEP users are more likely to be seen as HIVnegative, and therefore have a lower chance to transmit HIV, making them a more desirable sex partner [45,62]. While media outlets can present PrEP use in a stigmatizing way (i.e.…”
Section: Community Responsesmentioning
confidence: 99%